Inflammatory bowel diseases, the hygiene hypothesis and the other side of the microbiota: Parasites and fungi. (September 2020) - Panelli, Simona; Epis, Sara; Cococcioni, Lucia; Perini, Matteo; Paroni, Moira; Bandi, Claudio; Drago, Lorenzo; Zuccotti, Gian Vincenzo
Graphical abstract: Abstract: This review tackles the concept of the evolutionary mismatch, in relation with the reduction of the prevalence of the so-called "dirty old friends". These formed the variegated community of parasites and microorganisms, either prokaryotic or eukaryotic, that, over long evolutionary times, co-evolved with humans and their ancestors, inhabiting their digestive tracts, and other body districts. This community of microbial symbionts and metazoan parasites is thought to have evolved a complex network of inter-independence with the host, in particular in relation with their immune stimulating capacity, and with the consequent adaptation of the host immune response to this chronic stimulation. Strictly related to this evolutionary mismatch, the hygiene hypothesis, proposed by David Strachan in 1989, foresees that the increase in the incidence of inflammatory and autoimmune disorders during the twentieth century has been caused by the reduced exposure to parasites and microorganisms, especially in industrialized countries. Among these pathologies, inflammatory bowel diseases (IBDs) occupy a prominent role. From these premises, this review summarizes current knowledge on how variations in the composition of the gut bacterial microbiota, as well as its interactions with fungal communities, influence the overall immune balance, favouring or counteracting gut inflammation in IBDs. Additionally, the effect of worm parasites, either directly on the immune balance, or indirectly, through the modulation of bacterial and fungal microbiota, will be addressed. Finally, we will review a series of studies related to the use of molecules derived from parasitic worms and fungi, which hold the potential to be developed as postbiotics for the treatment of IBDs.